The child metaphor in "that hideous strength". - Lim, Beatrice Mei Chwee. (2009)
The image of the child is an intriguing one. The associations and connotations of the word ‘child’ occupy a wide spectrum, a spectrum which includes the esteemed quality of being sincere, to the detestable state of being weak and helpless. Thus it is possible to look upon a child with fondness and at the same time impose the importance of maturity on the child. Even divine authority, in the Christian tradition, tells us on one hand that one must become like a child to enter the kingdom of God, and on the other hand state that if you spare the rod, you will spoil the child (King James Bible, Prov. 13.24). The child comes to represent a sort of paradox figure, one which symbolizes a divinely-ordained model for humankind on one hand, and an underdeveloped being on the other. The multiple connotations of the child are explored in C.S. Lewis’ That Hideous Strength. The adult world of the novel appears to have hit a dead end, and the balm for such stagnation is a child, as revealed by Merlin (Lewis, THS 640). In the absence of a child, the society of Edgestow lacks a saviour who would have been the one to turn to in such tumultuous times. However, the child figure is not idealized to the point that the child is presented as perfect. The novel’s representation of the child is an ambiguous one, where on one hand, he signals a solution for a world in chaos because it does not have direction on how to achieve true progression, but on the other, representing one who has not yet established a clear code of principles for himself. However, this ambiguous treatment of the child in the novel leans more towards the healing powers of the child, and the message derived is that the child offers the redemption with which true progression can be achieved.